Significant pressure-induced enhancement of photoelectric properties of WS2 in the near-infrared region. Issue 8 (3rd August 2022) - Zhang, Xueting; Dong, Qing; Li, Zonglun; Jing, Xiaoling; Liu, Ran; Liu, Bo; Zhao, Tingting; Lin, Tao; Li, Quanjun; Liu, Bingbing
Abstract : Here, a WS2 -based photodetector is fabricated and its detection range is extended to optical communication waveband by pressure. At ambient pressure, WS2 exhibits a fast photoelectric response speed (rising/decaying time: 35/49 μs) under 635 nm laser illumination. Upon compression, the responsiveness and external quantum efficiency increase by two orders of magnitude under NIR illumination with different wavelengths as the pressure increases up to 17.2 GPa. The pressure-induced band gap reduction is mainly ascribed to the enhanced S-S interlayer interaction, leading to significant enhancement in the WS2 photoresponsiveness. This study paves the way for designing high-performance broadband photodetectors through pressure modification. IMPACT STATEMENT Fast photoelectric response speed and extended detection range were achieved in the WS2 -based photodetector via pressure modulation, which paves a new way for designing high-performance broadband photodetectors. GRAPHICAL ABSTRACT: UF0001